Electrocoagulation in Wastewater Treatment: A Comprehensive Review on Parameters and Applications - Nofri Naldi; Hazmi, Ariadi; Reni Desmiarti; Primas Emeraldi (Electrical Engineering Dept, Engineering Faculty, Universitas Andalas, 2025)
Electrocoagulation (EC) is a widely recognized and effective electrochemical treatment method used for removing various contaminants in liquid wastewater. It is capable of reducing a broad spectrum of pollutants, including heavy metals such as lead and cadmium, fluoride ions, dye molecules, oils, and pharmaceutical residues. The efficiency of EC depends on multiple parameters, including current density (which influences the rate of coagulation), pH level (affecting electrochemical reactions), electrode material (such as aluminum or iron), and the conductivity of the solution (which impacts energy consumption). Compared to conventional chemical coagulation processes, EC offers notable advantages by more effectively destabilizing fine colloidal particles, leading to faster aggregation and sedimentation, while consuming less energy. This review highlights recent technological advancements in EC applications, pointing out that most studies have been conducted at the batch scale, with relatively limited progress in developing continuous operation systems. The main challenges hindering large-scale implementation include electrode passivation (which reduces efficiency over time), sludge management issues, and the need for energy consumption optimization. To address these challenges, various strategies such as improving reactor design, developing hybrid treatment systems, and integrating EC with other processes are being explored. Overall, EC exhibits significant potential as a sustainable, flexible, and cost-effective technology for wastewater treatment. However, ongoing research is crucial to enhance the operational stability of continuous systems and ensure long-term sustainability, thereby facilitating broader industrial adoption of this promising technology.